2020
DOI: 10.1111/tbed.13591
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model as an efficacy test for foot‐and‐mouth disease vaccines

Abstract: Foot-and-mouth disease virus (FMDV) is a picornavirus belonging to the Aphthovirus genus (Soria et al., 2017). FMDV has seven distinct serotypes, namely O, A, C, SAT1, SAT2, SAT3 and Asia 1. This virus produces foot-and-mouth disease (FMD), a devastating and highly transmissible infection of farm animals, with large associated economic losses. Some countries are either FMD free or close to achieving eradication, while others are at an early stage of FMD control. In many countries, FMD control is performed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…The results of the humoral immune response profiles obtained in the murine model were further confirmed in calves, as was reported by Gnazzo et al (2020) (Gnazzo et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The results of the humoral immune response profiles obtained in the murine model were further confirmed in calves, as was reported by Gnazzo et al (2020) (Gnazzo et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, a prevalence of IgG1 and IgG2b isotypes was detected in animals vaccinated with VLPs-ISPA. These are promising results because Gnazzo et al (2020) reported that in the mouse model, IgG1 and IgG2b isotypes are important in the protection against FMDV O1 Campos\sout. VLPs-ISPA-vaccinated animals showed higher IgG3 isotype levels than the VLPs-CA group.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Twenty-four hours later, viremia was evaluated as described earlier. Animals were considered protected if viremia was absent at this time point, as established in previous studies (4)(5)(6)(14)(15)(16). Percentages of protection were calculated as 100× (protected/challenged mice).…”
Section: Inactivated Fmdv Dose To Vaccine Formulationmentioning
confidence: 99%